Role of tin as a reducing agent in iron containing heat absorbing soda-magnesia-lime-silica glass - Aman; Singh S.P. (My University, 2025)
The role of tin as a reducing agent in a 18Na 2O·2MgO·8CaO·72SiO2 glass containing a definite amount of total, σFe = [Fe2+] + [Fe3+], was investigated with different concentrations of total tin, σSn = [Sn2+] + [Sn4+], by absorption spectra of iron ions in the optical range 300-1200 nm recorded on a JASCO7800 spectrophotometer. The single broad absorption band for Fe2+ ion was marked at 1055 nm in the near infrared region and a narrow weak band for Fe3+ ion at its λmax at around 380 nm was observed in the silicate glass. The proportion of ferrous iron was found to increase in the glass in the beginning with the addition of tin up to 0-788% σSn and then it approached a maxima with 1-182% σSn. Further addition of tin was found to be futile for the constant iron concentration of 0-875% for achieving higher [Fe 2+]/[Fe3+] ratio for maximum heat absorption due to Fe2+ ion in the glass. The mechanism of the process was discussed on the basis of Sn2+/Sn4+ and Fe2+/Fe3+ mutual redox interaction in the molten glass at 1400°C. The suitable limit of tin was suggested to be 0-788 ≤ x ≤ 1.182% by wt for 0.875% of total iron for getting maximum ferrous ion in the glass.